PWE-179 Nutritional Assessment and Management in Patients with Decompensated Liver Disease. (4th June 2013) - Rogers, D; Gordon, V; Stewart, J; Tilley, C
Abstract : Introduction: Good nutrition is an effective intervention in decompensated liver disease 1 . Protein Energy Malnutrition (PEM) is found in 65–90% of patients with advanced liver disease and almost 100% of those awaiting transplant 1 . There is an association between nutritional status and mortality 1 and PEM before transplantation leads to higher rates of post-transplant complications. Reasons for PEM include ascites causing early satiety, alcohol use and malabsorption of fat soluble vitamins in cholestatic liver disease. Patients with cirrhosis have an altered metabolic response to starvation and overnight fasting can result in muscle depletion 2 . Daytime and evening snacks are therefore important, and hospital catering struggles to meet the nutritional needs of these patients. Clinicians should consider nutritional supplementation when admitting patients with cirrhosis. Methods: We audited 30 patients with decompensated liver disease who had been reviewed by a dietitian. Demographics, aetiology, prevalence of alcohol use and ascites were reviewed along with if the clerking or senior review doctor considered nutrition in their management plan. Dietetic reviews were audited to calculate the deficit in calorie and protein intake and if this was eliminated by the next review. Results: There were 18 male (60%) and 12 female (40%) patients with a mean age of 53 years (range 16–79). The most common aetiology was alcohol (25 patients) followed by Hepatitis C (2). 65% of those with alcoholic liver disease (ALD) were current drinkers (mean consumption 76 units/week, range 12–280). All non ALD aetiology were non-drinkers. Reason for admission was ascites (37%), alcoholic hepatitis (30%), encephalopathy (23%) and variceal bleeding (10%). 22/30 had ascites. No supplements or night time snacks were given and in only 3 was nutritional assessment planned. 18 (60%) were consuming under 500kcal/day and 15 (50%) were consuming under 10g of protein/day. 10 (33%) had a deficit of over 2000kcal/day and 12 (40%) had a protein deficit of over 80g/day. By the second visit the deficit had been eliminated in 8 (26%); 4 with supplements and 4 with NG feeding. 10 (34%) had a reduced deficit, 9 (30%) had no reduction and 3 patients had been discharged or died prior to review. Conclusion: We found a huge burden of PEM that is poorly recognised and acted upon. A Nutrition Care Pathway has been developed which should improve the nutritional care of these patients and encourage the use of supplements and snacks in addition to the hospital menu. Disclosure of Interest: None Declared. References: Henckel, AS, Buchman AL (2006) Nutritional support in chronic liver disease. Nature Clinical Practice Gastroenterology and Hepatology 3(4):202–9 The Nutrition and Hydration Digest: Improving Outcomes through Food and Beverage Services. British Dietetic Association (2012)